2008
DOI: 10.2196/jmir.1112
|View full text |Cite
|
Sign up to set email alerts
|

Development of Alive! (A Lifestyle Intervention Via Email), and Its Effect on Health-related Quality of Life, Presenteeism, and Other Behavioral Outcomes: Randomized Controlled Trial

Abstract: Background Cost-effective interventions to improve diet and physical activity are a public health priority. Alive! is an email-based intervention to increase physical activity, reduce saturated and trans fats and added sugars, and increase fruit and vegetable consumption. It was shown to improve these behaviors in a large randomized controlled trial.Objective (1) To describe the components and behavioral principles underlying Alive!, and (2) to report effects of the intervention on the secondary outcomes: heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 51 publications
(61 reference statements)
3
105
0
1
Order By: Relevance
“…Similar heterogeneous findings for the effect of a vegetarian dietary intervention on depression, anxiety, stress and general mood have been found based on discordant results per subscale of the psychological measurement tool used (99) . Other studies have been more varied in their approach, in that the interventions have targeted other lifestyle behaviours as well as FV intake, such as physical activity (100)(101)(102)(103)(104) . Findings are again inconsistent.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Similar heterogeneous findings for the effect of a vegetarian dietary intervention on depression, anxiety, stress and general mood have been found based on discordant results per subscale of the psychological measurement tool used (99) . Other studies have been more varied in their approach, in that the interventions have targeted other lifestyle behaviours as well as FV intake, such as physical activity (100)(101)(102)(103)(104) . Findings are again inconsistent.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Using simple proactive messages, delivered via SMS or email, has been used successfully in trials where consideration has been taken to smoking habits [17], physical activity [18] and weight loss [19]. Although slightly different in their nature, the main component of the interventions has been messages delivered continuously during a set time period.…”
Section: Introductionmentioning
confidence: 99%
“…Scores on the goal setting measure were below the midline for preparation and increased towards the midline in action and maintenance stages (See Figure 2), suggesting that individuals in higher stages of change more effectively use goal setting to progress to and maintain a higher stage of change. An intervention tailoring physical activity goals to individuals found similar results, in which individuals in the intervention group had a greater change towards a higher stage compared to the control group (Gladys et al, 2008). A study using the same goal setting measure (Exercise Goal-Setting Scale) found that increased goal setting behaviors successfully predicted increased PA behavior (Rovniak, Anderson, Winett, & Stephens, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…After six months of regular PA, a person has achieved the target behavior, and is in the maintenance stage. Research has shown differences in constructs such as SDT (Daley & Duda, 2006), self-efficacy for exercise , and goal setting (Gladys et al, 2008) across stages of change. It is hypothesized that individuals within a higher stage of change will have more adaptive scores across all constructs within the ESRM.…”
Section: Transtheoretical Model: Stages Of Changementioning
confidence: 99%